PSIKIS PROBLEMS OF THE CHARACTER OF BARRA SADEWA IN NOVEL HABIBIE YA NOUR EL AIN KARYA MAYA LESTARI GF - Anisa, Tria; Laila, Aruna; Tatalia, Ricci Gemarni (Universitas Andalas, 2021)
This research is motivated by the existence of psychological problems described by the author in the novel Habibie Ya Nour El Ain by Maya Lestari GF. The formulation of the problem in this study is, how are the psychological problems of the character Barra Sadewad in the novel Habibie Ya Nour El Ain by Maya Lestari GF. In accordance with the formulation of the problem, the purpose of this study is to describe the psychological problems of the character Barra Sadewa in the novel Habibie Ya Nour El Ain by Maya Lestari GF. The type and method of this research are qualitative research and descriptive methods of analysis. The data in this study are words and sentences related to psychological problems in the novel Habibie Ya Nour El Ain by Maya Lestari GF. The results of this study indicate that in the novel Habibie Ya Nour El Ain by Maya Lestari GF there are psychological problems experienced by the character Barra Sadewa. The psychological problems in the novel Habibie Ya Nour El Ain by Maya Lestari GF are depression, obsession, anxiety, guilt, inadequacy, anger, hurt, dissatisfaction, and concern. Some of the psychological problems that occur in the novel Habibie Ya Nour El Ain by Maya Lestari GF are depression which dominates the occurrence of psychological problems in characters. The cause of depression in the character in the novel Habibie Ya Nour El Ain by Maya Lestari GF is feeling disappointed with her life and presence which her parents did not want.